Analisis Penerapan Earned Value Management (EVM) dalam Pengendalian Proyek Sistem Informasi: Studi Literatur - Mey Wulandari Simanullang; Siska Dentina Pasaribu (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The high failure rate of information system projects in Indonesia where only 27% of projects are successfully completed on time and within budget reflects weak project control mechanisms. This study aims to analyze the effectiveness of applying Earned Value Management (EVM) in the control of information system projects and to identify the benefits and challenges of its implementation. The method used is a literature review of various relevant previous studies. The results of the study indicate that EVM integrated into web-based information systems or digital dashboards can improve the accuracy of real-time cost and schedule monitoring through indicators such as PV, EV, AC, CPI, and SPI, thereby supporting early detection of deviations and faster decision-making. However, its implementation still faces challenges in the form of limited managerial competence, planning biases, and organizational resistance to data transparency. This study concludes that the success of EVM is determined not only by technology but also by the readiness of human resources and managements commitment to transparent project governance.